MODEL WEBSITE PERSONAL BRANDING DOSEN SEBAGAI RUANG KARYA ILMIAH DAN MEDIA PEMBELAJARAN DIGITAL - efitra efitra; Nelwi Guswarni; Ahmad Louis Edward.V (JSR : Jaringan Sistem Informasi Robotik, 2022)
Abstract Website is an important media owned by a lecturer as Personal Branding. The digital era of website media is able to introduce or promote scientific works produced by lecturers globally, and as a digital learning media. The track record of a lecturer is no longer limited to carrying out tridharma activities, then these activities are only routine reports. Currently, the need for personal brands in building self-reputation. A lecturer needs to have media in the form of a website so that he can appear more professional and have social relations in the community. The media website can be used by lecturers with the main purpose as Lecturer Personal Branding, Lecturer Scientific Work Information Room and Digital Learning Media. Website model development uses descriptive analysis, starting from Requirements Analysis, Design, Development and Testing. Overall, the lecturer's personal branding website model begins with the initial collection of data such as lecturer data, lecturer branding names, teaching material data, lecturer's work data and others, to the creation of the lecturer's main domain name, setting the Domain Name System (DNS) on the server so that it can be accessed. through the internet network (online), Making Lecturer Profiles, uploading Scientific Works and posting articles. The design uses context diagrams. The implementation of the lecturer webiste model is presented in full with its features, consisting of the main visitor page, the Tridarma feature, the Lecturer's Work feature, the Lecturer Career feature, the Lecturer Guidelines feature, the Information feature, the Service feature and the News feature. With this Lecturer Personal Branding Website Model, it is to make it easier for lecturers, students, and the public to access related information. The hope is that in the future there will be many other lecturers who are interested in creating the same website as a lecturer's personal branding website.Keywords  :  Model, Website Dosen,  Personal Branding, Media Digital.  AbstrakWebsite merupakan media yang penting dimiliki oleh seorang dosen sebagai Personal Branding. Era digital media website mampu memperkenalkan atau mempromosikan karya-karya ilmiah yang dihasilkan dosen secara global, dan sebagai media pembelajaran digital. Rekam jejak seorang dosen tidak lagi sebatas menjalankan aktifitas tridarma, lalu aktifitas tersebut hanya sebagai laporan rutinitas. Saat ini, kebutuhan merek pribadi dalam membangun reputasi diri. Seorang dosen perlu memiliki media berupa website agar dapat terlihat tampil lebih profesional serta memiliki hubungan sosial di tengah masyarakat. Media website dapat dimanfaatkan oleh dosen dengan tujuan utama sebagai Personal Branding Dosen, Ruang Informasi Karya Ilmiah Dosen dan Media Pembelajaran Digital. Pengembangan model website menggunakan analisis deskriptif, dimulai dari Requirements Analysis, Desain, Develoment dan Testing. Secara keseluruhan model website personal branding dosen dimulai pengumpulan awal data seperti data dosen, nama branding dosen, data bahan ajar, data karya dosen dan lain-lain, hingga pembuatan nama domain utama dosen, pengaturan Domain Name System (DNS) pada server agar dapat diakses melalui jaringan internet (online), Membuat Profil Dosen, upload Karya Ilmiah dan posting Artikel. Perancangan menggunakan diagram konteks. Implementasi model website dosen disajikan secara lengkap fitur-fiturnya, terdiri dari halaman utama pengunjung, fitur Tridarma, fitur Karya Dosen, fitur Karir Dosen, fitur Pedoman Dosen, fitur Informasi, fitur Layanan dan fitur Berita. Dengan adanya Model Website Personal Branding Dosen ini agar mempermudah dosen, mahasiswa, dan masyarakat untuk mengakses informasi terkait. Harapannya agar model website personal branding dosen ini kedepannya banyak juga dosen lain yang tertarik untuk membuat website yang sama, sebagai website personal branding dosen.Kata kunci : Model, Website Dosen,  Personal Branding, Media Digital.